Chemically resistant composite membrane for fine bubble diffuser and process for making the same

CN122912697APending Publication Date: 2026-10-16SHANGHAI DUBHE ENVIRONMENTAL PROTECTION &TECH CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202611323301.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-08-28
Publication Date
2026-10-16

AI Technical Summary

Technical Problem

[0003]目前,商品化微孔曝气膜片的主体材料为三元乙丙橡胶(EPDM),EPDM具有成本适中、弹性好、耐臭氧及耐热老化等优点,但其耐油、耐溶剂、耐强酸强碱性能不足

Benefits of technology

本发明通过等离子体活化EPDM表面并接枝γ-氨丙基三乙氧基硅烷,与氟橡胶硫化过程中形成的活性位点发生共价键合,解决EPDM与氟橡胶热力学不相容导致的界面剥离问题;利用1H,1H,2H,2H-全氟辛基三甲氧基硅烷对气相白炭黑进行氟烷基改性,显著降低其表面能,实现纳米粒子在涂层中的分散与化学锚固,同步提升了涂层的力学强度和孔壁抗塌陷能力;碳酸氢铵在硫化过程中原位热解释放气体,一步形成微纳多孔结构;全氟聚醚油通过真空灌注确保多孔层完全填充,利用其超低表面能、化学惰性及与氟橡胶骨架的物理缠结,构建出稳定的超滑界面,从热力学上阻止油污、微生物及钙垢的黏附,同时降低气泡剪切阻力。最终制得的复合膜兼具EPDM的柔韧性、氟橡胶的耐化学性以及抗污染功能,显著延长了微孔曝气盘在复杂废水中的使用寿命并降低了运行能耗。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
Patent Text Reader

Abstract

The application relates to a chemical-resistant composite membrane for a microporous aeration disc and a preparation process thereof, and belongs to the technical field of sewage treatment. The chemical-resistant composite membrane is an EPDM base and a fluororubber coating layer coated on the surface of the base; the formula of the fluororubber coating layer is as follows: 90-100 parts of fluororubber raw rubber, 1.5-2.5 parts of bisphenol AF vulcanizing agent, 0.5-1.0 parts of accelerator, 8-20 parts of perfluoropolyether oil, 15-30 parts of ammonium bicarbonate, 5-10 parts of modified fumed white carbon black and 200-300 parts of methyl isobutyl ketone are used as the weight parts; the preparation process is that the EPDM base is subjected to plasma treatment and is sprayed with gamma-aminopropyl triethoxysilane, then the fluororubber slurry is coated, ammonium bicarbonate is decomposed to form a micro-nano porous structure through pre-vulcanization and secondary vulcanization, and finally perfluoropolyether oil is vacuum perfusion and is centrifuged to remove oil. The composite membrane prepared by the application has good chemical resistance and low fouling amount, so that the service life of the aeration disc in wastewater is prolonged.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the field of wastewater treatment technology and relates to a chemical-resistant composite membrane for microporous aeration discs and its preparation process. Background Technology

[0002] Microporous aeration discs are key oxygenation devices in wastewater treatment systems, with their core component being an elastic diaphragm. The diaphragm has micron-sized pores that open under air pressure to release tiny bubbles, and close elastically to prevent sludge backflow when aeration stops. Therefore, the diaphragm material must possess excellent elasticity, fatigue resistance, chemical corrosion resistance, and surface fouling resistance.

[0003] Currently, the main material of commercially available microporous aeration membranes is ethylene propylene diene monomer (EPDM) rubber. EPDM has advantages such as moderate cost, good elasticity, ozone resistance, and heat aging resistance, but its resistance to oil, solvents, and strong acids and alkalis is insufficient. When treating oily wastewater, dyeing and printing wastewater, chemical wastewater, or high-hardness wastewater, EPDM membranes are prone to swelling, shrinkage, plasticizer extraction, calcium scale deposition, and microbial adhesion, leading to increased bubble diameter, decreased oxygenation efficiency, and even membrane cracking and failure.

[0004] To improve chemical resistance, existing technologies have attempted to coat the surface of EPDM with a fluororubber layer. Fluororubber exhibits excellent resistance to fuels, solvents, strong acids, and various chemicals. However, its polarity differs significantly from that of EPDM, and the two are thermodynamically incompatible. If fluororubber is directly coated onto the EPDM surface, the interfacial bonding strength is low. Under fatigue conditions caused by repeated opening and closing of the aeration membrane, the coating is prone to peeling or cracking, making it unsuitable for long-term use.

[0005] On the other hand, even with a fluororubber coating, membranes still face the problems of scaling and biofilm adhesion. In wastewater containing calcium and magnesium ions, carbon dioxide stripping during aeration promotes the deposition of calcium carbonate on the membrane surface; in oily wastewater, oil easily adheres to the membrane surface and clogs micropores; in activated sludge processes, microorganisms readily proliferate on the membrane surface to form biofilms; these foulings significantly increase aeration resistance, leading to increased energy consumption and requiring frequent shutdowns for cleaning. Summary of the Invention

[0006] To address the shortcomings of existing technologies, the present invention aims to provide a chemical-resistant composite membrane for microporous aeration discs and its preparation process, which has the characteristics of good chemical resistance.

[0007] The objective of this invention can be achieved through the following technical solutions: A chemical-resistant composite membrane for microporous aeration discs, wherein the chemical-resistant composite membrane is an EPDM matrix and a fluororubber coating applied to the surface of the matrix. The formulation of the fluororubber coating is as follows, by weight: 90-100 parts of fluororubber raw rubber, 1.5-2.5 parts of bisphenol AF vulcanizing agent, 0.5-1.0 parts of accelerator, 8-20 parts of perfluoropolyether oil, 15-30 parts of ammonium bicarbonate, 5-10 parts of modified fumed silica, and 200-300 parts of methyl isobutyl ketone.

[0008] As a preferred embodiment of the present invention, the accelerator is benzyltriphenylphosphine chloride.

[0009] As a preferred embodiment of the present invention, the modified fumed silica is obtained by surface modification of fumed silica with 1H,1H,2H,2H-perfluorooctyltrimethoxysilane, wherein the amount of 1H,1H,2H,2H-perfluorooctyltrimethoxysilane used is 3 to 5% of the mass of fumed silica.

[0010] As a preferred embodiment of the present invention, the fluororubber coating surface has a micro-nano porous structure with a pore size of 0.5~3μm and a porosity of 40~60%.

[0011] A process for preparing a chemical-resistant composite membrane for microporous aeration discs, the specific steps of which are as follows: S5-1: The surface of the EPDM substrate is subjected to plasma treatment, sprayed with an ethanol solution containing γ-aminopropyltriethoxysilane, and dried at 70~80℃ for 10~20min to obtain the pretreated EPDM substrate; S5-2: Add fluororubber raw rubber, bisphenol AF vulcanizing agent, accelerator, and modified fumed silica to methyl isobutyl ketone, disperse for 10-30 min, then add ammonium bicarbonate and continue dispersing for 30-60 min to obtain the coating slurry; S5-3: Apply the coating slurry to the surface of the pretreated EPDM substrate, with a wet film thickness of 150~200μm; S5-4: Pre-vulcanize at 100~120℃ and 0.3~0.6MPa for 5~15min, then vulcanize at 170~190℃ and normal pressure for 20~40min; S5-5: Immerse the vulcanized composite film in perfluoropolyether oil, inject it under vacuum for 10-30 minutes, and centrifuge to remove oil for 2-5 minutes to obtain the chemical-resistant composite film.

[0012] As a preferred embodiment of the present invention, the plasma treatment power in S5-1 is 100~200W and the time is 2~5min.

[0013] As a preferred embodiment of the present invention, the amount of γ-aminopropyltriethoxysilane added in S5-1 is 1 to 2% of the mass of the ethanol solution.

[0014] As a preferred embodiment of the present invention, the dispersion speed in S5-2 is 1200~1500 rpm.

[0015] As a preferred embodiment of the present invention, the vacuum degree in S5-5 is -0.08 to -0.098 MPa, and the injection temperature is 30 to 50°C.

[0016] As a preferred embodiment of the present invention, the centrifugal speed in S5-5 is 500~800 rpm.

[0017] Plasma treatment of the EPDM surface generates high-energy electrons and free radicals, breaking the CH and C=C bonds in the EPDM molecular chain and introducing polar oxygen-containing functional groups. Simultaneously, surface etching increases roughness. γ-aminopropyltriethoxysilane undergoes ethoxylation in an aqueous ethanol solution to generate silanol, which condenses with functional groups on the EPDM surface, anchoring the amino group to the EPDM surface. During fluororubber vulcanization, bisphenol AF, under the action of the accelerator benzyltriphenylphosphine chloride (BPP), generates a nucleophile, which undergoes a deHF reaction with the vinylidene fluoride units on the fluororubber chain to form conjugated double bonds, and then undergoes nucleophilic substitution crosslinking with the phenolic hydroxyl groups of bisphenol AF. Simultaneously, the amino group can react with intermediates generated during fluororubber vulcanization to form covalent bonds, achieving chemical bonding between the fluororubber coating and the EPDM matrix.

[0018] Fumed silica surfaces are rich in silanol groups. The methoxy groups of 1H,1H,2H,2H-perfluorooctyltrimethoxysilane condense with these silanol groups after hydrolysis, branching perfluoroalkyl groups onto the silica surface. This modification significantly reduces the surface energy of the silica, making its solubility parameters closer to those of fluororubber. Uniformly dispersed fumed silica forms physical cross-linking points through interfacial chemical bonds, while the particles themselves inhibit crack propagation. This improves the dispersibility of silica in fluororubber slurries, preventing agglomeration and enhancing the mechanical properties of the coating: nanoparticles fill the micropore walls, strengthening the porous structure and preventing pore wall collapse or wear.

[0019] Ammonium bicarbonate begins to decompose at 60–100°C. During the pre-vulcanization stage, gas is generated and forms bubbles in the viscous rubber matrix. Secondary vulcanization cross-links and fixes the fluororubber, while gas escapes, leaving open channels. Pressure control prevents excessive bubble coalescence. The final result is a micro / nano structure with a pore size of 0.5–3 μm and a porosity of 40–60%, exhibiting capillary effect and capable of stably storing lubricant. This process eliminates the need for expensive and complex equipment such as photolithography and etching, employing a one-step pyrolysis-based pore-forming method that is simple and compatible with rubber vulcanization.

[0020] Perfluoropolyether molecules have extremely low surface energy and a similar chemical structure to the porous framework of fluororubber. They are firmly adsorbed into the pore walls through van der Waals forces and physical entanglement, making them difficult to displace by water or oil. After infusion, a lubricating film forms on the surface. When oil droplets, microorganisms, calcium scale, and other contaminants come into contact with the surface, the contaminants are preferentially repelled by the perfluoropolyether oil and are difficult to adhere to. At the same time, the lubricating film significantly reduces the frictional resistance when bubbles detach, which can effectively reduce aeration energy consumption.

[0021] The beneficial effects of this invention are: This invention addresses the interfacial delamination problem caused by the thermodynamic incompatibility between EPDM and fluororubber by plasma-activating the EPDM surface and grafting γ-aminopropyltriethoxysilane, which covalently bonds with the active sites formed during the vulcanization of fluororubber. Furthermore, it utilizes 1H,1H,2H,2H-perfluorooctyltrimethoxysilane to fluoroalkylate-modify fumed silica, significantly reducing its surface energy and enabling the dispersion and chemical anchoring of nanoparticles in the coating, simultaneously improving the coating's mechanical strength and pore wall anti-collapse ability. Ammonium bicarbonate undergoes in-situ thermal decomposition during vulcanization, releasing gas and forming a micro-nano porous structure in one step. Perfluoropolyether oil is vacuum-infused to ensure complete filling of the porous layer, utilizing its ultra-low surface energy, chemical inertness, and physical entanglement with the fluororubber skeleton to construct a stable, ultra-slippery interface. This thermodynamically prevents the adhesion of oil, microorganisms, and calcium deposits, while simultaneously reducing bubble shear resistance. The resulting composite membrane combines the flexibility of EPDM, the chemical resistance and antifouling properties of fluororubber, significantly extending the service life of the microporous aeration disc in complex wastewater and reducing operating energy consumption. Detailed Implementation

[0022] To further illustrate the technical means and effects of the present invention in achieving its intended purpose, the following detailed description of the specific implementation methods, structures, features, and effects of the present invention, in conjunction with embodiments, is provided below.

[0023] In the following examples and proportions, the fluororubber raw material was purchased from Daikin Industries, Ltd., Japan, model DALEL G-801. It should be noted that, unless otherwise specified, the source of the raw materials used in the following examples is not specifically limited; commercially available products or products prepared using conventional methods well-known to those skilled in the art are acceptable. Experimental methods without specific conditions are all conventional methods and conditions well-known in the art.

[0024] Example 1

[0025] A chemical-resistant composite membrane for microporous aeration discs, wherein the chemical-resistant composite membrane is an EPDM matrix and a fluororubber coating applied to the surface of the matrix. The formulation of the fluororubber coating is as follows, by weight: 95 parts of fluororubber raw rubber, 2 parts of bisphenol AF vulcanizing agent, 0.8 parts of accelerator, 15 parts of perfluoropolyether oil, 22 parts of ammonium bicarbonate, 8 parts of modified fumed silica, and 250 parts of methyl isobutyl ketone. The accelerator is benzyltriphenylphosphine chloride; The modified fumed silica was obtained by surface modification of fumed silica with 1H,1H,2H,2H-perfluorooctyltrimethoxysilane, wherein the amount of 1H,1H,2H,2H-perfluorooctyltrimethoxysilane used was 4% of the mass of the fumed silica. A process for preparing a chemical-resistant composite membrane for microporous aeration discs, the specific steps of which are as follows: S5-1: The surface of the EPDM substrate is subjected to plasma treatment in an oxygen atmosphere with a power of 150W for 3.5 minutes. An ethanol solution containing γ-aminopropyltriethoxysilane is sprayed on the substrate, wherein the amount of γ-aminopropyltriethoxysilane added is 1.5% of the mass of the ethanol solution. The substrate is then dried at 75°C for 15 minutes to obtain the pretreated EPDM substrate. S5-2: Add fluororubber raw rubber, bisphenol AF vulcanizing agent, accelerator, and modified fumed silica to methyl isobutyl ketone, disperse for 20 min at a dispersion speed of 1300 rpm, then add ammonium bicarbonate and continue dispersing for 45 min to obtain the coating slurry. S5-3: The coating slurry is applied to the surface of the pretreated EPDM substrate, and the wet film thickness is 180μm; S5-4: Pre-vulcanize at 110℃ and 0.4MPa for 10min, then vulcanize at 180℃ and normal pressure for 30min; S5-5: The vulcanized composite membrane is immersed in perfluoropolyether oil, and then injected under vacuum conditions for 20 minutes. The vacuum degree is -0.09MPa and the injection temperature is 40℃. The membrane is then centrifuged for 3 minutes to remove oil at a centrifugation speed of 700rpm to obtain the chemical-resistant composite membrane.

[0026] Example 2

[0027] The only difference between this embodiment and Embodiment 1 is that the formulation of the fluororubber coating is as follows, calculated by weight: 90 parts of fluororubber raw rubber, 1.5 parts of bisphenol AF vulcanizing agent, 0.5 parts of accelerator, 8 parts of perfluoropolyether oil, 15 parts of ammonium bicarbonate, 5 parts of modified fumed silica, 200 parts of methyl isobutyl ketone, and the rest are the same as in Embodiment 1.

[0028] Example 3

[0029] The only difference between this embodiment and Embodiment 1 is that the formulation of the fluororubber coating is as follows, calculated by weight: 100 parts of fluororubber raw rubber, 2.5 parts of bisphenol AF vulcanizing agent, 1.0 part of accelerator, 20 parts of perfluoropolyether oil, 30 parts of ammonium bicarbonate, 10 parts of modified fumed silica, and 300 parts of methyl isobutyl ketone. The rest are the same as in Embodiment 1.

[0030] Example 4

[0031] The only difference between this embodiment and Example 1 is that the modified fumed silica is obtained by surface modification of fumed silica with 1H,1H,2H,2H-perfluorooctyltrimethoxysilane. The amount of 1H,1H,2H,2H-perfluorooctyltrimethoxysilane used is 3% of the mass of fumed silica. All other aspects are the same as in Example 1.

[0032] Example 5

[0033] The only difference between this embodiment and Example 1 is that the modified fumed silica is obtained by surface modification of fumed silica with 1H,1H,2H,2H-perfluorooctyltrimethoxysilane. The amount of 1H,1H,2H,2H-perfluorooctyltrimethoxysilane used is 5% of the mass of fumed silica. All other aspects are the same as in Example 1.

[0034] Example 6

[0035] The only difference between this embodiment and Embodiment 1 is that the plasma treatment power in S5-1 is 100W and the time is 5min; all other aspects are the same as in Embodiment 1.

[0036] Example 7

[0037] The only difference between this embodiment and Embodiment 1 is that the plasma treatment power in S5-1 is 200W and the time is 2min; all other aspects are the same as in Embodiment 1.

[0038] Comparative Example 1 The only difference between this comparative example and Example 1 is that no modification treatment is performed on the fumed silica; all other aspects are the same as in Example 1.

[0039] Comparative Example 2 The only difference between this comparative example and Example 1 is that ammonium bicarbonate is not added; otherwise, they are the same as in Example 1.

[0040] Comparative Example 3 The only difference between this comparative example and Example 1 is that perfluoropolyether oil is not injected; otherwise, they are the same as in Example 1.

[0041] Chemical resistance test Medium: ① Toluene; ② 10wt% NaOH solution; ③ 10wt% H2SO4 solution; Immerse at 70℃ for 7 days, test the tensile elongation at break of the sample according to GB / T 528-2009 standard, and calculate the elongation at break retention rate compared with the initial sample.

[0042] Anti-scaling performance test Test water sample: CaCl2 500 mg / L + vegetable oil emulsion 500 mg / L + tap water, pH=8.0±0.2, temperature 25±2℃. Operating conditions: continuous aeration, air flow rate 2 L / min, water depth 1.2 m, water replenished and pH adjusted daily, operation for 90 days, aeration discs removed, dried at 60℃ for 24 h, total mass weighed; then the surface was brushed with a stiff brush, dried again and weighed to obtain the mass of sediment; further calculation of scaling amount (mg / cm³) was performed. 2 = Sediment mass / Effective membrane area; The specific experimental results are summarized in the table below.

[0043]

[0044] As shown in the data from Examples 1-3 above, Example 1 achieves a good balance between chemical resistance and anti-scaling performance, exhibiting the best overall performance. Comparing the data from Examples 4 and 5 with Example 1, it can be seen that Examples 4 and 5 are close to Example 1 in all indicators but slightly inferior, with Example 5 showing a scaling amount of 0.12 mg / cm³. 2 The toluene retention rate was 86%, which is better than in Example 4, indicating that a fluorosilane dosage of 4-5% can achieve good results, but 4% is more optimal. Comparison of the data from Examples 6 and 7 with Example 1 shows that the retention rates and scaling amounts in Examples 6 and 7 are lower than those in Example 1. Specifically, the toluene retention rate in Example 6 decreased to 80%, while the scaling amount increased to 0.20 mg / cm³. 2 Example 7: Toluene retention rate 82%, scale buildup 0.18 mg / cm³ 2 This indicates that plasma power and time need to be matched; insufficient activation due to low power leads to interfacial bonding defects, increasing the risk of solvent penetration and fouling. Comparative Example 1, using unmodified silica, showed a significant decrease in tensile property retention to 68% under toluene conditions, and lower tensile property retention under acid and alkali conditions compared to all other examples, with increased fouling. This suggests that unmodified silica agglomeration leads to coating defects, becoming channels for solvent penetration and fouling adhesion points. Fluorosilane modification is crucial for maintaining coating density and chemical resistance. Comparative Example 2, without the addition of ammonium bicarbonate, did not show a significant decrease in chemical resistance, but the fouling amount increased sharply to 0.52 mg / cm³. 2The concentration of perfluoropolyether in Comparative Example 3, which was significantly higher than in all other examples, indicates that in-situ surface pore formation creating a porous micro / nano structure to store the perfluoropolyether imparts a long-lasting anti-fouling effect to the coating. In Comparative Example 3, without perfluoropolyether oil injection, the fouling concentration was as high as 0.65 mg / cm³. 2 This indicates that adding perfluoropolyether can effectively achieve long-term stain resistance and scale prevention.

[0045] The above description is merely a preferred embodiment of the present invention and is not intended to limit the present invention in any way. Although the present invention has been disclosed above with reference to preferred embodiments, it is not intended to limit the present invention. Any person skilled in the art can make some modifications or alterations to the above-disclosed technical content to create equivalent embodiments without departing from the scope of the present invention. Any simple modifications, equivalent changes and alterations made to the above embodiments based on the technical essence of the present invention without departing from the scope of the present invention are still within the scope of the present invention.

Claims

1. A chemical-resistant composite membrane for microporous aeration discs, characterized in that, The chemical-resistant composite film consists of an EPDM matrix and a fluororubber coating applied to the surface of the matrix. The formulation of the fluororubber coating is as follows, by weight: 90-100 parts of fluororubber raw rubber, 1.5-2.5 parts of bisphenol AF vulcanizing agent, 0.5-1.0 parts of accelerator, 8-20 parts of perfluoropolyether oil, 15-30 parts of ammonium bicarbonate, 5-10 parts of modified fumed silica, and 200-300 parts of methyl isobutyl ketone.

2. The chemical-resistant composite membrane for microporous aeration discs according to claim 1, characterized in that, The accelerator is benzyltriphenylphosphine chloride.

3. The chemical-resistant composite membrane for microporous aeration discs according to claim 1, characterized in that, The modified fumed silica is obtained by surface modification of fumed silica with 1H,1H,2H,2H-perfluorooctyltrimethoxysilane, wherein the amount of 1H,1H,2H,2H-perfluorooctyltrimethoxysilane used is 3 to 5% of the mass of fumed silica.

4. The chemical-resistant composite membrane for microporous aeration discs according to claim 1, characterized in that, The fluororubber coating has a micro-nano porous structure with a pore size of 0.5~3μm and a porosity of 40~60%.

5. A process for preparing a chemical-resistant composite membrane for a microporous aeration disc as described in any one of claims 1 to 4, characterized in that, The specific steps of the preparation process are as follows. S5-1: The surface of the EPDM substrate is subjected to plasma treatment, sprayed with an ethanol solution containing γ-aminopropyltriethoxysilane, and dried at 70~80℃ for 10~20min to obtain the pretreated EPDM substrate; S5-2: Add fluororubber raw rubber, bisphenol AF vulcanizing agent, accelerator, and modified fumed silica to methyl isobutyl ketone, disperse for 10-30 min, then add ammonium bicarbonate and continue dispersing for 30-60 min to obtain the coating slurry; S5-3: Apply the coating slurry to the surface of the pretreated EPDM substrate, with a wet film thickness of 150~200μm; S5-4: Pre-vulcanize at 100~120℃ and 0.3~0.6MPa for 5~15min, then vulcanize at 170~190℃ and normal pressure for 20~40min; S5-5: Immerse the vulcanized composite film in perfluoropolyether oil, inject it under vacuum for 10-30 minutes, and centrifuge to remove oil for 2-5 minutes to obtain the chemical-resistant composite film.

6. The preparation process of a chemical-resistant composite membrane for a microporous aeration disc according to claim 5, characterized in that, The plasma treatment in S5-1 has a power of 100~200W and a time of 2~5min.

7. The preparation process of a chemical-resistant composite membrane for a microporous aeration disc according to claim 5, characterized in that, The amount of γ-aminopropyltriethoxysilane added in S5-1 is 1-2% of the mass of the ethanol solution.

8. The preparation process of a chemical-resistant composite membrane for a microporous aeration disc according to claim 5, characterized in that, The dispersion speed in S5-2 is 1200~1500 rpm.

9. The preparation process of a chemical-resistant composite membrane for a microporous aeration disc according to claim 5, characterized in that, The vacuum degree in S5-5 is -0.08 to -0.098 MPa, and the injection temperature is 30 to 50°C.

10. The preparation process of a chemical-resistant composite membrane for a microporous aeration disc according to claim 5, characterized in that, The centrifugal speed in S5-5 is 500~800 rpm.